2019
DOI: 10.1038/s41385-019-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective delipidation of Mycobacterium bovis BCG enables direct pulmonary vaccination and enhances protection against Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis ( M.tb ), the causative agent of tuberculosis (TB), is the leading killer due to an infectious organism. Mycobacterium bovis bacillus Calmette-Guérin (BCG) is the only vaccine approved against TB, however, its efficacy against pulmonary TB is poor. While BCG is currently inoculated intradermally, the natural route of M.tb infection is through the lung. Excessive lung pathology caused by pulmonary inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 46 publications
1
31
1
Order By: Relevance
“…This scenario has been tested in studies where the BCG vaccine has been exposed to human ALF and subsequently used to vaccinate mice showing that ALF-exposed BCG has an altered cell envelope and increased protection against M. tuberculosis challenge (183). Based on this study where ALF modified the BCG cell envelope and drove improved protection, studies delipidating BCG mostly removing apolar lipids showed the ability of this delipidated BCG to be delivered directly into the lung, minimizing tissue inflammation and to further increase protection against M. tuberculosis infection and significantly reducing tissue damage, the hallmark of TB disease (184). All these studies put in trial the role of the M. tuberculosis glycolipids during infection, how M. tuberculosis metabolically adapts to the lung environment, how M. tuberculosis uses its cell envelope glycolipids to mask its presence to host cells or to confuse them by mimicking mammalian structures, and how M. tuberculosis reconstitutes and reorganizes its cell envelope during infection and in the different environments that may encounter within the host.…”
Section: The Role Of Cell Envelope Glycolipids In M Tuberculosis Evomentioning
confidence: 99%
“…This scenario has been tested in studies where the BCG vaccine has been exposed to human ALF and subsequently used to vaccinate mice showing that ALF-exposed BCG has an altered cell envelope and increased protection against M. tuberculosis challenge (183). Based on this study where ALF modified the BCG cell envelope and drove improved protection, studies delipidating BCG mostly removing apolar lipids showed the ability of this delipidated BCG to be delivered directly into the lung, minimizing tissue inflammation and to further increase protection against M. tuberculosis infection and significantly reducing tissue damage, the hallmark of TB disease (184). All these studies put in trial the role of the M. tuberculosis glycolipids during infection, how M. tuberculosis metabolically adapts to the lung environment, how M. tuberculosis uses its cell envelope glycolipids to mask its presence to host cells or to confuse them by mimicking mammalian structures, and how M. tuberculosis reconstitutes and reorganizes its cell envelope during infection and in the different environments that may encounter within the host.…”
Section: The Role Of Cell Envelope Glycolipids In M Tuberculosis Evomentioning
confidence: 99%
“…For example, exposure of BCG to human alveolar lining fluid, to expose underlying epitopes, resulted in improved BCG protection in mice [88]. Selective removal of inflammatory lipids from BCG rendered it more protective and resulted in less lung pathology compared to conventional BCG when delivered mucosally in mice [89].…”
Section: Bcg and Attenuated Whole-cell Live Vaccinesmentioning
confidence: 99%
“…https://doi.org/10.1101/2020.02.25.964312 doi: bioRxiv preprint 5 influx of neutrophils with bactericidal activity [11] and increased CD4 + T cell recruitment to the lung after M. tuberculosis infection [12]. Vaccines inducing high levels of pulmonary IL-17 have demonstrated efficacy against M. tuberculosis in different animal models [13,14] although balancing the protective and pathogenic roles of IL-17 in the lung is a critical consideration [15].…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly detrimental in the case of M. tuberculosis infection, where priming and recruitment of effector T lymphocytes to the lungs is delayed, allowing unchecked growth of the organism [24,25]. For this reason, mucosal vaccination has been of interest in the field of TB vaccines, with pulmonary delivery of BCG [14,26], live recombinant viruses [8,27,28], or protein/adjuvants [29,30] resulting in protective immune responses. When administered to the respiratory mucosa, highly inflammatory adjuvanted vaccines may induce protective immunity, but this is often accompanied by excessive inflammation, mucus accumulation and eosinophilia [31].…”
mentioning
confidence: 99%